Slum upgrading and inclusive municipal governance in Harare, Zimbabwe: New perspectives for the urban poor. (August 2015) - Muchadenyika, Davison
Abstract: The story of the urban poor in Harare and Zimbabwean cities in general is a story of evictions, fear and misery. In May 2005, at the behest of the Government of Zimbabwe the infamous Operation Restore Order, a house demolition campaign left more than 700 thousand people homeless. Nearly a decade later, there are increased opportunities for improvement and change in the lives of the urban poor in Harare, Zimbabwe's capital city. The purpose of the paper is to present how the Harare Slum Upgrading Programme is creating and strengthening municipal and community partnerships to tackle city challenges in an inclusive manner. This research indicates the housing struggles of the urban poor and the emerging City-community engagement in urban services provision (water, sanitation, tenure security and roads) and changing municipal attitudes towards the urban poor. In particular, the article presents participatory urban planning and development, slum upgrading institutional structure, profiling and enumeration, and slum upgrading impacts (resilience of the urban poor, living in slums without fear, expansive pool of beneficiaries, review of planning regulations and land ownership) as major issues promoting inclusive municipal governance. Inclusivity is implemented through incremental development, which is allowing people to settle on land first and access municipal services gradually over time. Two main factors explain such positive steps towards inclusive governance in Harare. First are indications of gradual institutional change in which the City of Harare's governance culture is changing through 'opening up' and embracing the urban poor. Second, over the years, the urban poor have built a strong and vibrant alliance which is acting as a medium of participation in City governance. The paper concludes that slum upgrading sustainability at city-wide level requires active City participation and institutionalisation as opposed to a project based approach. Lastly, addressing concerns of the urban poor is susceptible to political contestations, requiring strong impartiality to counter such forces. Highlights: Participatory slum upgrading promotes inclusive municipal governance. Inclusive municipal governance strengthens municipal and community partnerships. Political will is vital in changing municipal attitudes towards the urban poor.